A POLÍCIA MILITAR DO PARANÁ FRENTE A DESASTRES SOCIOAMBIENTAIS: Estratégias e Limites para o Desenvolvimento Comunitário - Zarpelon, Fabio Antonio Matucheski (2021)
The topic of socioenvironmental disasters has been gaining importance in the latest years, on one side because of the exponential increase in quantity and severity of the events and on the other side, mainly because of the interdisciplinary approach incited by courses like Environmental History, Environmental Sociology or Risk Analysis. The current work discusses the realization of river monitoring in the state of Paraná from the second half of the XX century, considering this process within Anthropocene Great Acceleration scope, and the dilemmas concerning the emergence of a risky society. Some discursive convergences are found in the construction of dams in the state, especially the national and regional developmentalism combined with the technocratic perspective of governance of the natural world. To address the theme, an interdisciplinary perspective was adopted which brings Environmental History, Police Studies and Communitarian Development closer, considering the brute force technology concept as an interpretation vector for the relations made among state, community and natural world regarding the rivers and the emergence of environmental risks. All that set out from a local analytic and exemplifying observation, in which Military Police of the state of Paraná and the Governador Bento Munhoz da Rocha Netto Hydroelectric Power Plant – Foz do Areia – are a part of, inserting them in the civil defense context, thus allowing to perceive the existent risk of alleged dam rupture. Facing the risk scenario, a natucultural approach that breaks the existent dualisms and achieves the dichotomy fusion amongst nature and culture, considering the resultant hybridization between mankind and nature, has the capacity of breaking the vicious cycle caused by guilt imposition, and that leads to problematizing, involving all workers, with focus on dealing with the existent risk in an effective way. Likewise, it is necessary for the police to think and act differently, focusing mainly on prevention and participation of all involved to identify, prioritize and solve problems, which goes along with the Communitarian Police philosophy and strategy. All of these connections enable the wok of natucultural building of formal and informal prevention to socioenvironmental disasters, which consequently enables the sustainable communitarian development in its three dimensions, being them economic, social and environmental.